Convergence among EU regions (1990-2001) : quality of national institutions and "objective 1" status - Freitas, Miguel Lebre de (2003)
This article focuses on convergence in terms of output per working-age person across regions in the European Union for the period 1990-2001. Controlling for the quality of national institutions, we investigate whether the status of “objective 1” region improves the speed of convergence as compared to what would be expected, given the regions’ initial conditions. We find evidence of conditional convergence among EU regions, with the quality of national institutions having a positive impact, but no evidence on a correlation between the eligibility for objective 1 and faster convergence.